THE MAIN ASPECTS OF LABORATORY DIAGNOSTICS IN URGENT SURGERY - Sergey I. Kubanov; Yury Y. Pykhtin; Albina B. Kubanova (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to studying of timely laboratory diagnostics questions of purulent - septic pathology in surgery. On the example of leukocyte index of intoxication calculation at an acute appendicitis efficiency of the automatic hematologic analysis in an assessment of pyoinflammatory process existence, a tendency to change definition of a percentage ratio of different leukocytes pools is shown.